Introduction - Macdonald, Michael C.A. (Proceedings of the Seminar for Arabian Studies, 2018)
Most of the papers published in this volume were presented at a Special Session of the fifty-first Seminar for Arabian Studies held at the British Museum on 5 August 2017. Its subject was ‘Languages, scripts, and their uses in ancient North Arabia’ and it was held to celebrate the completion in the previous March of Phase 2 of the ‘Online Corpus of the Inscriptions of Ancient North Arabia’ (OCIANA).